(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2023)
Protein kinases are the focus of several drug discovery initiatives across the globe because genetic changes such as mutations, overexpression, translocations, and dysregulation of these enzymes contribute to the pathophysiology of numerous diseases. Of the 80 small molecule protein kinase inhibitors that the FDA has authorized, 77 are oral bioavailable medications. According to the information, 69 of these medications are authorized to treat neoplasms, including solid tumors like lung and breast cancer as well as non-solid tumors like leukemia. The remaining 11 medications also target non-neoplastic conditions such ulcerative colitis, rheumatoid arthritis, and psoriasis. The FDA label was used to calculate the dose and quantity of pills needed daily, and the cost of the medications was retrieved from www.pharmacychecker.com. Any government or private insurance coverage, which would pay the whole cost or, more likely, a portion of the advertised price, is not included in this technique. Treatment of neoplastic illnesses averaged 17,900 a month, with futibatinib (used to treat cholangiocarcinomas with FGFR2 fusions) costing 44,000 and binimetinib (melanoma) costing at least 5100. With a high of 17,000 for belumosudil (graft vs. host disease) and a minimum of 200 for netarsudil eye drops (glaucoma), the average monthly cost for treating non-neoplastic disorders was 6800. The incidence of the targeted condition is negatively correlated with the cost of the medications. Since there are less than 200,000 possible patients in the US, several of these medications are or were categorized as orphan pharmaceuticals.